2022
DOI: 10.18184/2079-4665.2022.13.1.8-26
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Corporate Culture for the Sustainability of Companies in the Context of Crisis Phenomena

Abstract: Purpose: the purpose of the article is to study the role of corporate culture in the sustainability of companies in the conditions of crisis phenomena, as well as to analyze methodological approaches to corporate culture as a tool for the competitive success of the company.Methods: the methodology of the work is based on the use of the concepts of organizational culture and sustainable development, as well as the theory of modernization, integrating economic growth and the culture of companies within a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Fang, Ma and Lei [8] showed that the values contained in corporate culture can have a significant impact on the sustainability of their enterprises. Izmailova [9] 's research shows that corporate culture plays a dual role in the sustainable development of enterprises. Companies should establish a culture that not only motivates employees, promotes innovation, but also ensures efficient operations and market competitiveness.…”
Section: Corporate Culture and Sustainable Developmentmentioning
confidence: 99%
“…Fang, Ma and Lei [8] showed that the values contained in corporate culture can have a significant impact on the sustainability of their enterprises. Izmailova [9] 's research shows that corporate culture plays a dual role in the sustainable development of enterprises. Companies should establish a culture that not only motivates employees, promotes innovation, but also ensures efficient operations and market competitiveness.…”
Section: Corporate Culture and Sustainable Developmentmentioning
confidence: 99%